2004
DOI: 10.1094/cchem.2004.81.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ferulic Acid and Catechin on Sorghum and Maize Starch Pasting Properties

Abstract: The effects of ferulic acid and catechin on starch pasting properties were studied as part of an investigation into the structure and functionality of phenolics in starch‐based products. Commercial maize starch, starches from sorghum cultivars (SV2, Chirimaugute, and DC‐75), and the phenolic compounds ferulic acid and catechin were used in the investigation. Pasting properties were measured using rapid viscosity analysis. Ferulic acid and catechin (up to 100 mg each) were added to maize or sorghum starch (3 g,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 25 publications
2
52
1
Order By: Relevance
“…The addition of ferulic acid decreased hot paste viscosity, final and setback viscosities, but had no influence on the peak viscosity of maize and wheat starches [17,18]. The hardness and adhesiveness of the starch gel with addition of ferulic acid reduced as compared to that of the native wheat starch [18].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The addition of ferulic acid decreased hot paste viscosity, final and setback viscosities, but had no influence on the peak viscosity of maize and wheat starches [17,18]. The hardness and adhesiveness of the starch gel with addition of ferulic acid reduced as compared to that of the native wheat starch [18].…”
Section: Introductionmentioning
confidence: 93%
“…Several studies on effects of addition of phenolic acids, especially ferulic acid, on pasting and textural properties of starch have been also done [17,18]. The addition of ferulic acid decreased hot paste viscosity, final and setback viscosities, but had no influence on the peak viscosity of maize and wheat starches [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins with disulfide bonds may restrict starch granule swelling during gelatinization, and Zhang and Hamaker [101] reported that dithiothreitol, a reducing agent, treatment of sorghum flour influenced RVA pasting profiles. Moreover, phenolic compound was also reported to influence starch pasting properties [17]. Instructively, Liu, et al [102] showed that SMBS significantly (p < 0.001) reduced all five starch viscosity parameters and graded SMBS supplementation linearly reduced final starch viscosities (r = −0.986; p < 0.001).…”
Section: Rva Starch Pasting Profilesmentioning
confidence: 98%
“…Also ferulic acid has been shown to influence starch pasting profiles which implies phenolic acids have the capacity to interact with starch [17]. Thompson and Yoon [56] found tannic acid depressed wheat starch digestion in vitro and Thompson, et al [57] reported intakes of phenolic compounds by humans were negatively correlated with blood glycaemic indices.…”
Section: "Non-tannin" Polyphenolic Compounds and Phenolic Acidsmentioning
confidence: 99%
“…Ferulic acid is the dominant phenolic acid in sorghum but it is also found in barley, maize, triticale and wheat (Kandil et al 2012). Interestingly, ferulic acid has been shown to influence starch pasting profiles as determined by rapid visco-analysis of maize and sorghum, which suggests that phenolic acids have the capacity to interact with starch (Beta and Corke 2004). Also, Hung et al (2013) reported that ferulic acid has the capacity to complex with debranched starch and that these starch-ferulic acid complexes were associated with increases in resistance of starch to digestion.…”
Section: Discussionmentioning
confidence: 99%